Analysis of the D-shaped PCF-based SPR sensor using Resonance Electron Relaxation and Fourier domain method. (July 2023) - Luo, Wei; Li, Xuejin; Abbasi, Syeda Aimen; Zhu, Shaodi; Ho, Ho-Pui; Yuan, Wu
Highlights: High-precision analysis for the Surface Plasmon Resonance sensor based on D-shaped photonic crystal fiber. Resonance Electron Relaxation is defined to explain the 'S-shape' profile in the dispersion. Each signal component is identified with Fourier transform algorithm progress. Abstract: Since the D-shaped photonic crystal fiber (PCF) based Surface Plasmon Resonance (SPR) sensor is an important tool in scientifical research and applications, a new concept of Resonance Electron Relaxation (RER) is defined to investigate its detection property. It successfully explains the 'S-shape' profile in the dispersion and the wavelength delay between the dispersion intersection and loss peak. The birefringence interference has also been analyzed with the RER phenomenon. Then we experimentally demonstrated the SPR sensing performance. A fast Fourier transform (FFT) algorithm is applied in the experiment to separate each component signal in the spatial frequency domain. Then using a band passing filter of 0.001–0.006 nm −1 together with inverse FFT algorithm, the distinguished SPR spectrum shows a significant agreement with theoretical simulations, with differences of only 14.3 nm and 1.48% in resonance wavelength and intensity. This study facilitates a high precision analysis and data process approach for the SPR sensor based on D-shaped PCF and presents greatly promising application prospects in SPR sensors.